Buckling strength of GTT NO96 LNG Carrier cargo containment system. (15th April 2018) - Park, Young IL; Lee, Jong Hyun
Abstract: The present study investigates the design buckling capacities of a Gaztransport and Technigaz (GTT) NO96-type liquefied natural gas (LNG) cargo containment system (NO96 CCS), one of the most critical failure modes for a box-type LNG cargo containment system, against sloshing dynamic loads from an LNG carrier cargo tank. The design load for NO96 CCS (sloshing) is a typical dynamic event; hence, the dynamic effect on the buckling capacity is investigated as the defining dynamic strength factor. A series of finite-element (FE) analyses for the insulation system are performed using commercial FE software (i.e., ABAQUS and ANSYS) and considering the environmental temperature and material properties of the system. The design buckling strength under both static and dynamic conditions is provided based on the FE calculations and compared with the as-designed criteria of DNV GL for a membrane-type LNG cargo tank. Highlights: Linear buckling capacities of NO96 CCS against 12 loaded areas with 4 types of CCS. Developing design dynamic strength factor (DSF) to calculate dynamic buckling strength of NO96 CCS. Developing design dynamic buckling capacities of NO96 CCS against various rise time of sloshing load and 4 types of CCS. Comparison of dynamic buckling capacities of NO96 CCS between DNVGL's method and current study.